Battery Anodes: Core–Shell Ge@Graphene@TiO2 Nanofibers as a High‐Capacity and Cycle‐Stable Anode for Lithium and Sodium Ion Battery (Adv. Funct. Mater. 7/2016). (February 2016) - Wang, Xiaoyan; Fan, Ling; Gong, Decai; Zhu, Jian; Zhang, Qingfeng; Lu, Bingan
Abstract : Germanium@graphene@TiO2 core–shell nanofibers are obtained through electrospinning, followed by atomic layer deposition, by B. Lu and co‐workers. On page 1104, they describe how this can be used as an anode material for lithium and sodium ion batteries. Graphene and TiO2 can doubly protect the structure of the germanium nanofibers during the charge and discharge processes. As an anode material, the composite exhibits high capacities and good cycling stability.